1989
DOI: 10.1007/bf01967564
|View full text |Cite
|
Sign up to set email alerts
|

Distribution ofHaemophilus influenzae andHaemophilus parainfluenzae biotypes isolated from the human genitourinary tract

Abstract: A total of 3,598 genital specimens from men and women was cultured for Haemophilus spp. using a simple selective culture method. Two hundred and thirty three samples (6.5%) were positive for Haemophilus spp., 216 Haemophilus parainfluenzae and 28 Haemophilus influenzae strains being isolated. Biotyping demonstrated that Haemophilus parainfluenzae biotype II was dominant at all sites, especially the male urethra, comprising 59% of all Haemophilus strains isolated. On the other hand, Haemophilus influenzae bioty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Although rare, H. influenzae biotype IV have been implicated as the cause of non-invasive infections in humans, including urogenital infections Alrawi et al (2002); Harper and Tilse (1991); Quentin et al (1989) and neonatal sepsis Van Dcynse et al 2016; Wallace et al (1983) and have been found to colonise the nasopharynx of children Jain et al (2006) and the adult urinary tract Drouet et al (1989). Importantly, ampicillin resistance within H. influenzae biotype IV has been observed Jain et al (2006); Rashid et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, H. influenzae biotype IV have been implicated as the cause of non-invasive infections in humans, including urogenital infections Alrawi et al (2002); Harper and Tilse (1991); Quentin et al (1989) and neonatal sepsis Van Dcynse et al 2016; Wallace et al (1983) and have been found to colonise the nasopharynx of children Jain et al (2006) and the adult urinary tract Drouet et al (1989). Importantly, ampicillin resistance within H. influenzae biotype IV has been observed Jain et al (2006); Rashid et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among extrapulmonary infections, genital infections have scarcely been reported, although recent studies have considered Haemophilus species to be potential pathogens in genitourinary infections including bartholimits (1,2). Among extrapulmonary infections, genital infections have scarcely been reported, although recent studies have considered Haemophilus species to be potential pathogens in genitourinary infections including bartholimits (1,2).…”
Section: Haemophilus Influenzae Bartholinitismentioning
confidence: 99%
“…The prevalence of Haemophilus influenzae in the genital tract is low (0.7-3.5 %), and consistently higher in the male urethra than in cervicovaginal secretions (2). Genitourinary colonization by this organism can originate either from the upper respiratory tract or gastrointestinal tract.…”
Section: Haemophilus Influenzaementioning
confidence: 99%
“…However, some NTHi biotype IV strains, often referred to as "H. influenzae biotype IV" or "H. influenzae cryptic genospecies," and now provisionally named "Haemophilus quentini," constitute a distinct group of potential urogenital pathogens implicated in maternal and neonatal infections (8)(9)(10)(11).…”
mentioning
confidence: 99%